The social consequences of population displacement in Ukraine: the risks of marginalization and social exclusion - Mykhnenko, V; Kuznetsova, I; Mikheieva, O; Gulyieva, G; Dragneva, R (Zenodo, 2018)
Soon after de facto annexation of the Crimean Peninsula by the Russian Federation in February-March 2018, the Donbas was plunged into a brutal – albeit undeclared or ‘hybrid’ – war that pitted Russia and its proxy military forces against Ukraine. In total, between 14 April 2014 and 15 November 2017, the UN recorded 35,081 war-related casualties, including 10,303 people killed and 24,778 injured. Today, there are 1 491 528 internally displaced people or 1 217 071 families, most of them from war-torn territories (Ministry for Social Policy 23 March 2018). Over 80% of the IDPs have found temporary residence in just ve Ukrainian regions: the government-controlled districts of Donetsk and Luhansk oblasts (42% and 13% respectively), the neighbouring Kharkiv and Zaporizhia oblasts (10.9% and 7.4% respectively), and Kyiv (8%). Of the remaining Donbas inhabitants, two to three million currently reside in non-government controlled areas, with another 600,000 being caught in the so-called ‘grey zone’, living within 5km either side of the 457km frontline.